Correction: (P-135) Double enamel pearl whit buds: a case report - Özkan, G; Akkoç, Rf; Demirdaş, K; Artaş, G; Ögetürk, Murat (Anatomi ve Klinik Anatomi Derneği, 2016)
Author names for abstract of poster presentation published in Volume 10, Supplement 2, September 2016, page 178 – P-135 “Double enamel pearl whit buds: a case report” is erroneously published as: Özkan G1, Akkoç RF1, Demirdaş K2,Ögetürk M1. Corrected version is as follows: Özkan G1, Akkoç RF1, Demirdafl K2, Artaş G3, Ögetürk M1.
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi